2021
DOI: 10.3390/ijerph181910356
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Proprioceptive Control versus Visual Control on Reaction Speed, Hand Coordination, and Lower Limb Balance in Young Students 14–15 Years Old

Abstract: Currently, sports activities require a high reaction speed, coordination, and balance, highlighting the relationship between proprioceptive control, visual control, and hand–eye coordination in youth. The present research assessed the proprioceptive control, reaction speed, and lower limb balance of youth from five different schools to identify the level of physical preparation of children in this direction. This prospective study was conducted between 1 January, 2020, and 29 February, 2020. A total of 107 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…In this regard, Neto et al [ 31 ] reported significant differences in RT values between males and females (males: 243 ± 67 ms, females: 342 ± 50 ms, p = 0.011), whereas, after a hand–eye RT test, Reigal et al [ 14 ] reported an average difference of 46.9 ms between males and females. Furthermore, Szabo et al [ 32 ] reported significant differences after applying the Ruler Drop Test, which assesses hand–eye reaction speed when comparing males and females in the dominant hand ( p = 0.095). In this study, which evaluated males and females aged 14–15 years, no significant differences were found between genders when comparing reaction speed in the non-dominant hand ( p = 0.095).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, Neto et al [ 31 ] reported significant differences in RT values between males and females (males: 243 ± 67 ms, females: 342 ± 50 ms, p = 0.011), whereas, after a hand–eye RT test, Reigal et al [ 14 ] reported an average difference of 46.9 ms between males and females. Furthermore, Szabo et al [ 32 ] reported significant differences after applying the Ruler Drop Test, which assesses hand–eye reaction speed when comparing males and females in the dominant hand ( p = 0.095). In this study, which evaluated males and females aged 14–15 years, no significant differences were found between genders when comparing reaction speed in the non-dominant hand ( p = 0.095).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, which evaluated males and females aged 14–15 years, no significant differences were found between genders when comparing reaction speed in the non-dominant hand ( p = 0.095). [ 32 ]. Contrary to this evidence, Vences de Brito et al [ 17 ] found evidence that female Shotokan karateka had better RT than males practicing the same sport (male: 292 ± 30 ms, female: 288 ± 20 ms, p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proprioceptive control has long been essential for improving sports performance, medical disorders, everyday life activities, or further sports performance. Some specialists associated the proprioceptive control with somatosensory or proprioceptive deficiencies with effects on movement regulation that can develop from early ages (Coleman et al, 2001;Goble et al, 2009;Zwicker et al, 2013;Li et al, 2015), is linked with a low level of movement and sports practice (Szabo et al, 2021). These capacities were associated with the sense of relative location and movement of the limbs and body (Konczak, 2009) and needed in any human activity.…”
Section: Introductionmentioning
confidence: 99%